Essay Review: On the Borderland of Physics and Psychic Phenomena: Physics and Psychics: The Occult and the Sciences in Modern Britain by Richard Noakes - Alvarado, Carlos S. (Journal of Scientific Exploration, 2021)
In an address presented on August 20, 1891 at the Sixty-First Meeting of the British Association for the Advancement of Science the President of the Association’s Section of Mathematics and Physical Science discussed various scientific developments. The speaker started with brief mentions of Michael Faraday’s centenary, and the death of Wilhelm Weber, and then went on to detailed discussions of a binary system of stars, the discovery of ways to achieve color photography, and the importance of professional systematic physics research leaving behind amateur efforts. Then he changed directions and said he was going to discuss a “topic which is as yet beyond the pale of scientific orthodoxy” (p. 551). The topic, the study of psychic phenomena, was called by the speaker the “borderland of physics and psychology,” an area “bounded on the north by psychology, on the south by physics, on the east by physiology, and on the west by pathology and medicine” (p. 553). “I have spoken,” our speaker continued, “of the apparently direct action of mind on mind, and of a possible action of mind on matter. But the whole region is unexplored territory . . . I care not what the end may be. I do care that inquiry shall be conducted by us” (p. 555, my italics). The speaker was English physicist Oliver J. Lodge (1892; see Figure 1), who by that time was well known for his interest and work in psychical research.1 The “us” in the last quote above was a reference to the community of physicists. Such interest in the topic by some physicists, of which Lodge was a main player, is the subject of the book reviewed here.